2013
DOI: 10.1111/prd.12031
|View full text |Cite
|
Sign up to set email alerts
|

Expression of odontogenic ameloblast‐associated and amelotin proteins in the junctional epithelium

Abstract: Two novel proteins - odontogenic ameloblast-associated protein and amelotin - have recently been identified in maturation-stage ameloblasts and in the junctional epithelium. This article reviews the structure and function of the junctional epithelium, the pattern of expression of odontogenic ameloblast-associated and amelotin proteins and the potential involvement of these proteins in the formation and regeneration of the junctional epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Immunogold labeling characterized by transmission electron microscopy showed that early in the maturation stage AMTN penetrates into the enamel surface and seems to concentrate in the less-mineralized crypts left behind as the ameloblasts retracted their Tomes’ processes at the end of the secretory stage [20]. By late maturation AMTN localizes specifically to the ameloblast-enamel interface and then disappears beneath the late, reduced enamel epithelium [20], only to reappear at the cell-enamel interface beneath the junctional epithelium following tooth eruption [29,30] where it is believed to facilitate adherence of the junctional epithelium to the tooth surface [31]. AMTN interacts with itself and with ODAM [32] and colocalizes with ODAM in the basal lamina beneath maturation stage ameloblasts and junctional epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogold labeling characterized by transmission electron microscopy showed that early in the maturation stage AMTN penetrates into the enamel surface and seems to concentrate in the less-mineralized crypts left behind as the ameloblasts retracted their Tomes’ processes at the end of the secretory stage [20]. By late maturation AMTN localizes specifically to the ameloblast-enamel interface and then disappears beneath the late, reduced enamel epithelium [20], only to reappear at the cell-enamel interface beneath the junctional epithelium following tooth eruption [29,30] where it is believed to facilitate adherence of the junctional epithelium to the tooth surface [31]. AMTN interacts with itself and with ODAM [32] and colocalizes with ODAM in the basal lamina beneath maturation stage ameloblasts and junctional epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Nishio et al. , the epithelium of the dento–gingival junction probably plays a central role in maintaining periodontal health. Working out the protective role played by specific molecules in junctional and crevicular epithelia would seem to be a productive approach for developing new antidestructive therapeutics.…”
Section: Normal Periodontium and Homeostasismentioning
confidence: 86%
“…Accordingly, an improved understanding of the molecules that mediate epithelial attachment to teeth could provide new insights into pathogenic mechanisms in periodontitis and may yield high-value targets for prevention and therapeutic intervention. Consistent with this notion, Nishio et al (19) have explored cell-adhesion molecules that mediate attachment of gingival epithelium to the tooth surface, focussing on the expression of odontogenic and ameloblast-associated molecules, such as amelotin, in the junctional epithelium. Here they consider the structure and the function of the junctional epithelium and how the pattern of expression of these molecules impacts the formation and regeneration of the junctional epithelium in wound healing.…”
Section: Normal Periodontium and Homeostasismentioning
confidence: 99%
“…AMTN protein is continuously detected at the ameloblast-enamel interface from the maturation through the reduced enamel epithelium to the JE in mice (Somogyi-Ganss et al, 2012) and rats (Moffatt et al, 2006b; Nishio et al, 2013). The localization of AMTN in the JE is restricted to the cell/mineral interface, while ODAM is localized in a pericellular fashion in the JE.…”
Section: Roles In the Junctional Epitheliummentioning
confidence: 99%